Fractal characterization of pore structure and its influence on salt ion diffusion behavior in marine shale reservoirs. (30th October 2020) - Meng, Mianmo; Ge, Hongkui; Shen, Yinghao; Ji, Wenming
Abstract: Hydraulic fracturing becomes a significant way to develop fossil hydrogen energy from marine shale. Some marine shale formations have a higher salt ion concentration in flowback fluid, about which the mechanism is still unclear. In this study, both the fractal characterization of pore structure and its influence on salt ion diffusion was researched. The fractal dimension D 1 can reflect the roughness of pore surface, and the fractal dimension D 2 can reflect the complexity of pore structure. The fractal dimension D 1 of Sichuan Niutitang Formation is only 2.0069 and the ones of other shale samples are between 2.5291 and 2.6341, which means that the pore surface of Sichuan Niutitang Formation is far smoother than the ones of other samples. The fractal dimension D 2 ranges from 2.7396 to 2.9546, which indicates that all samples have complex pore structure. The salt ion diffusion rate is mainly controlled by specific surface area, median pore-throat radius and clay content. A higher specific surface area provides more surface for the interaction between liquid and matrix, and lots of salt ion was released into imbibed liquid. A larger median pore-throat radius benefits to salt ion diffusing out of sample, thus a higher salt ion diffusion rate appears. The liquid can cause the clay-swelling which has the potential to reduce the salt ion diffusion channel, thus the higher the clay content, the lower the salt ion diffusion rate. Our research is conducive to understanding the fractal characterization of marine shale and its impact on high salt ion concentration in flowback fluid. Highlights: Marine shale has a rougher pore surface and complex pore structure. The initial salt ion diffusion rate is influenced by the complexity of pore structure which is mainly controlled by clay content, TOC, specific surface area and median pore-throat radius.